Audience Perception Of YouTube Podcast Content' Login ' Episode 12 - Wibowo, Mohammad Satriyo; Rochmania, Ainur (Procedia of Social Sciences and Humanities, 2024)
This study aims to examine audience perceptions of the "Login" program broadcast on Deddy Corbuzier's YouTube channel as a medium for da'wah and education. The study employs the S-O-R (Stimulus-Organism-Response) theory, which explores the perception process through three main stages: sensation, attention, and response. The findings indicate that the "Login" program consistently captures the audience's attention, as evidenced by the high frequency and duration of viewing. The program is able to meet the audience's need for information and entertainment, which in turn enhances their level of attention. Respondents also reported that the show not only entertains but also provides new insights and influences their views on the topics discussed. Overall, the "Login" program successfully shapes strong perceptions among viewers through the S-O-R process, where the stimulus from the show effectively captures attention and influences audience responses, both emotionally and cognitively. This suggests that the "Login" program can function effectively as a medium for conveying messages of da'wah and education